Improving the tourists’ experience - Gonçalves, F. (2019)
The Internet of Things (IoT) is part of a new paradigm where it is possible to integrate every sensor to the Internet, allowing it to be even more immersive and pervasive. Mastering these technologies, such as pervasive and smart places, is a challenge, especially when the goal is to achieve a closer interaction between citizens and applications. The rapid development and exciting innovation create an opportunity to stimulate a variety of new tools for tourists. Taking into account the versatility of IoT sensors for different applications, in this position paper we outline our perspective of ambient intelligence in smart tourism.